Acute phase proteins and oxidative stress before and after treatment in neonatal calves with sepsis caused by Escherichia coli K99 - Akyüz, E; Merhan, O; Sezer, M; Coşkun, MR; Erkılıç, EE; Batı, YU; Bozukluhan, K; Kuru, M; Şahin, M; Gökce, G (Journal of the Hellenic Veterinary Medical Society, 2025)
This study aimed to detect changes in acute-phase proteins endothelin-1 (ET-1), pentraxin-3 (P-3), ceruloplasmin (Cp), haptoglobin (Hp), and albumin, in calves with diarrhea caused by Escherichia coli K99 neonatal sepsis before and after treatment. Diagnostic and prognostic clinical, biochemical, and hematological parameters were evaluated. The sepsis group was composed of 20 newborn calves which met neonatal sepsis criteria, did not receive any treatment, and were referred to the clinics within 24 hours after the detection of clinical findings. The control group consisted of 10 healthy calves for comparison. Clinical examinations were performed before (0th h) and after (7th d) treatment. Blood samples were drawn via the jugular vein from sick calves before and after treatment and once from control animals. The P-3, ET-1, Cp, Hp, and malondialdehyde (MDA) concentrations in the sepsis group before treatment were statistically higher than post-treatment and control group values (P<0.05); while the glutathione (GSH) concentration was statistically lower (P<0.05). In conclusion, the high pre-treatment concentrations of P-3, ET-1, Cp, Hp, and MDA in the sepsis group were of diagnostic importance. The approximation of these parameters after treatment to the mean values of the control group was also of prognostic value. Keywords: Calf; Ceruloplasmin; Haptoglobin; Sepsis diagnostic biomarkers